Determinan Daya Tarik Investasi di Kota Tasikmalaya Provinsi Jawa Barat - Ika Sartika (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
One of the objectives of regional autonomy is to increase regional competitiveness, which automatically increases the welfare of the people. According to the results of previous studies, regional competitiveness will increase if investment attractiveness is high. This means that many investors are interested in investing in the area. The city of Tasikmalaya which was founded in 2001 has a relatively low level of competitiveness compared to other younger areas, such as West Bandung Regency and Banjar City. According to a study by the Monitoring Committee for the Implementation of Regional Autonomy (KPPOD), the City of Tasikmalaya is not included in the ranking of the best cities in terms of investment attractiveness. This study aims to analyze the determinants of investment attractiveness to increase the competitiveness of the City of Tasikmalaya. This research was conducted with a quantitative and qualitative descriptive approach in accordance with the research objectives. Qualitative data were obtained through interviews with 17 informants who came from elements of the government and entrepreneurs from various sectors. The results of the interviews combined with the results of observations and secondary data are used to describe the investment attractiveness of the City of Tasikmalaya. Quantitative data analysis used a modified Analytical Hierarchy Process (AHP) model. The results obtained are the attractiveness of investment in the City of Tasikmalaya, especially in the tertiary sector with the dominant category of information and communication services. Meanwhile, the determinants of investment attractiveness in the City of Tasikmalaya based on the perceptions of entrepreneurs according to rank are regional economic aspects, institutions, physical infrastructure, socio-politics, as well as labor and productivity.